2021
DOI: 10.3389/fonc.2021.692142
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Induced Inflammatory Cytokines and the Emerging Diagnostic Devices for Cancer Detection and Prognosis

Abstract: Chronic inflammation generated by the tumor microenvironment is known to drive cancer initiation, proliferation, progression, metastasis, and therapeutic resistance. The tumor microenvironment promotes the secretion of diverse cytokines, in different types and stages of cancers. These cytokines may inhibit tumor development but alternatively may contribute to chronic inflammation that supports tumor growth in both autocrine and paracrine manners and have been linked to poor cancer outcomes. Such distinct sets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
157
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 193 publications
(161 citation statements)
references
References 186 publications
(223 reference statements)
2
157
1
1
Order By: Relevance
“…However, many other Th-2 cytokines were higher in C3 T1 than in C2 T1 . This observation stresses the concept that focusing on a single cytokine is not adequate, as cytokines interact with each other as previously reported [1].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, many other Th-2 cytokines were higher in C3 T1 than in C2 T1 . This observation stresses the concept that focusing on a single cytokine is not adequate, as cytokines interact with each other as previously reported [1].…”
Section: Discussionsupporting
confidence: 85%
“…The tumor microenvironment (TME) drives the dynamic interaction between tumor and immune cells, largely mediated by cytokines and chemokines that exert their biological actions even distantly moving through blood circulation, for instance supporting immunecell recruitment and cancer metastatization [1].…”
Section: Introductionmentioning
confidence: 99%
“…Within the tumor microenvironment, the OC cells and other stromal cells secrete proinflammatory cytokines, such as IL6 and others. Several studies have further shown that increased inflammation levels in the tumor microenvironment promote poorer prognosis for OC (reviewed in [22,29]). Here, we analyzed published articles in Medline and Embase databases that measured IL6 in the circulation and the peritoneal fluid of women with OC in order to provide fundamental baselines on the absolute concentration levels of IL6 in various stages of this disease, as well as to determine the potential of IL6 as a biomarker for not only the late-stage, but also for the detection of the early-stage OC, which is currently difficult to diagnose.…”
Section: Discussionmentioning
confidence: 99%
“…Ascitic IL6 thus has the potential to be used as a minimally-invasive diagnostic biomarker for OC. Biomarkers with high sensitivity and specificity that facilitate early detection will improve quality of life by increasing progression-free and overall survival of OC patients [27,29].…”
Section: Introductionmentioning
confidence: 99%
“…While they attract immune cells in the microenvironment (chemokines) or lead to the proliferation of immune cells, cytokines can also enhance oncogenic transformation, promote metabolic changes and hypoxia, thus favoring tumorigenesis. The cytokine-induced inflammatory response whose initial goal is to resolve the underlying insult can promote tumorigenesis as various molecular pathways are common to inflammation and carcinogenesis response pathways [82]. Following tumorigenesis, malignant cells can also secrete tumor-promoting cytokines, exerting their actions through autocrine mechanisms.…”
Section: Inflammation and Cancermentioning
confidence: 99%